Exceptionally rare site:the occurrence of pilomatricoma of the ear lobule - Gund, Tapasaya; Telang, Rahul A.; Yathati, Kireet; Kumar, Prakhar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Pilomatricoma, a rare benign tumor primarily affecting the head and neck region, presents diagnostic challenges and requires histopathological confirmation for accurate diagnosis. A case of pilomatricoma in a 70-year-old female with a chronic swelling on the Left ear lobule is reported. Surgical excision was performed, confirming the diagnosis histopathologically, highlighting the importance of accurate recognition and management. Timely surgical excision of pilomatricoma is crucial, with low recurrence rates reported. Accurate diagnosis aids in appropriate management and optimal patient outcomes.